Legal Harmonization for Energy Transitions: Embedding SDG 7 and Paris Agreement Norms in National Renewable Energy Law - Supangat, Ajis; Tridianto, Ari; Parwati, Anak Agung Dewi Intan; Simanungkalit, Robert L.; Saputra , Dedi (Legalis : Journal of Law Review, 2025)
Achieving Sustainable Development Goal 7 (SDG 7) requires integrating global legal commitments into national renewable energy laws. This article examines how international frameworks particularly SDG 7 and the Paris Agreement can be harmonized with domestic legal systems to accelerate renewable energy transitions. Using a doctrinal-comparative method, it analyzes the legal architectures of the European Union (EU), the United States (US), and Indonesia, focusing on binding targets, incentive models, and policy instruments. The EU’s rule-based system (RED III, REPowerEU) illustrates the effectiveness of legally mandated targets and fast-track permitting. In contrast, the US Inflation Reduction Act exemplifies a long-term incentive-based approach using technology-neutral tax credits (Sections 45Y and 48E) to de-risk renewable investment. Indonesia’s evolving hybrid model blends regulatory mandates (Perpres 112/2022), planning instruments (RUPTL), and strategic finance platforms (JETP-CIPP), though it faces challenges from regulatory instability, such as rooftop solar policy reversals. These case studies reveal that legal predictability is a key driver of investment and policy coherence. Hybrid legal frameworks in the Global South demonstrate the need for adaptable models that accommodate local governance realities while aligning with international norms. Embedding global standards into national law enhances policy legitimacy, investment security, and implementation effectiveness. The study concludes that harmonizing global and national legal systems through binding obligations, fiscal incentives, and transparent planning is essential for achieving SDG 7. It advocates for legal toolkits that combine enforcement, flexibility, and normative alignment to support inclusive, sustainable energy transitions.